Expanding our reach: marriage and family therapists in the public school system - Vennum, Amber V.; Vennum, Drew (My University, 2013)
As states change their legislation to include Marriage and Family Therapists (MFTs) as approved mental health providers in schools, it is important to understand the experiences of MFTs in this context to improve training and increase our effectiveness. MFTs with experience working in public schools (N = 21) discuss the advantages and rewards of working in schools, challenges they have experienced, how they have dealt with those challenges, and training they recommend for MFTs seeking to work in schools. Qualitative results have implications for practitioners, training, and supervision. The possibility of a specialization in School-Based Family Therapy is discussed.
Keywords: School-Based Family Therapy; Public schools; Training